Academic citizenship and wellbeing: An exploratory cross-cultural study of South African and Swedish academic perceptions - Coldwell, D; Papageorgiou, E; Callaghan, C; Fried, A (South African Journal of Higher Education, 2016)
Academic citizenship is, conceptually speaking, closely related to organisational citizenship behaviour, as both concepts can be regarded as consisting essentially of personal co-worker and organisational support behaviours. Academics across the world operate in widely divergent settings in different socioeconomic and political situations and higher education environments. Such differing circumstances might be expected to have a bearing on the priorities that academics face in different countries and the ways academic citizenship is understood. This paper uses a mixed methods approach to analyse perceptions of academic citizenship and employee well-being in one Swedish and one South African university which operate in starkly different socioeconomic circumstances. The findings of the exploratory study suggest that despite wide-ranging differences in socioeconomic environments between the two countries, there is a high degree of common understanding of the form and substance of academic citizenship and its bearing on well-being. Key words Academic citizenship, organisational citizenship behaviour, South African and Swedish universities, well-being